2014
DOI: 10.1177/1062860614531069
|View full text |Cite
|
Sign up to set email alerts
|

The Association Between Skilled Nursing Facility Care Quality and 30-Day Readmission Rates After Hospitalization for Heart Failure

Abstract: The objective of the study was to assess the association between care quality of skilled nursing facilities (SNFs) and 30-day risk-adjusted readmission rate (RAR) for patients with acute decompensated heart failure (ADHF). A retrospective cohort study was conducted involving 603 discharges from a tertiary care hospital to 17 SNFs after hospitalization for ADHF. SNF quality was assessed based on the CMS 5-star quality rating and a survey of SNF characteristics and processes of care. In all, 20% of cases were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
33
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(39 citation statements)
references
References 28 publications
5
33
1
Order By: Relevance
“…Our results extend previous studies (Unroe et al., ; Allen et al., ; Ogunneye, ; Sandvik et al., ; Russell et al., ; Veilleux et al., ; Tuso et al., ; Neuman et al., ), which focused on the association between nursing home performance and hospital readmissions at the patient level. For example, Ogunneye et al.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results extend previous studies (Unroe et al., ; Allen et al., ; Ogunneye, ; Sandvik et al., ; Russell et al., ; Veilleux et al., ; Tuso et al., ; Neuman et al., ), which focused on the association between nursing home performance and hospital readmissions at the patient level. For example, Ogunneye et al.…”
Section: Discussionsupporting
confidence: 90%
“…For example, Ogunneye et al. () studied the relationship between quality ratings of skilled nursing facilities and 30‐day risk‐adjusted readmission rate for 603 patients discharged from a single hospital to 17 skilled nursing facilities after hospitalisation for acute decompensated heart failure and found that the all‐cause readmission rate was 18% for higher quality and 22% for lower quality skilled nursing facilities. Our finding about that the staffing ranking score is the most important measure associated with readmission is consistent with the findings reported by Neuman et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The association between nursing home and home health performance in quality of care and outcomes has been studied . For example, one study found that individuals receiving care in higher‐quality skilled nursing facilities had lower readmission rates (18%) than those in lower‐quality skilled nursing facilities (22%) . Another study found that improving nursing home and home health performance was associated with lower community‐level risk‐standardized readmission rates .…”
Section: Discussionmentioning
confidence: 99%
“…Medicare‐certified home health agencies, which provide a comprehensive array of in‐home services, including home health aide assistance, social work, nursing, occupational therapy, physical therapy, and speech therapy, serve a critical role in caring for individuals receiving ongoing outpatient care or who have been discharged from a nursing home or hospital . High‐quality home health care can benefit individuals and health systems by improving individuals' health status and quality of life, shortening hospital stays, lowering hospital costs, and preventing unplanned readmissions . As the population in the United States ages and the number of elderly individuals grows (from 45 million in 2015 to a projected 84 million in 2050), the provision of high‐quality home health care is an increasingly important component of the U.S. healthcare system.…”
mentioning
confidence: 99%